Effect of reinforced particle size on wire EDM of MMCs. (2015) - Pramanik, A.; Basak, A.K.; Islam, M.N.
This paper investigates the effect of the size of reinforced particles on wire electrical discharge machining (EDM) of metal matrix composites (MMCs) in terms of material removal rate (MRR), surface integrity and wear of wire electrodes (WEs). It was found that larger particles significantly reduced the MRR, as they were better able to protect the matrix material from EDM sparks compared to smaller particles. The machined surfaces were full of solidified melted matrix, splashes of melted material, cavities and blisters, which are not significantly affected by particle size. Spattering and splashing might have contributed to the transfer of materials between the WE and the MMCs. The diameter of the WE was reduced nonlinearly with the increased size of the reinforced particles after machining. The smallest reduction in electrode diameter occurred in the unreinforced matrix material.